Uterine perforation during uterine repositioning on nonpuerperal uterine inversion by delivery of a large fibroid: A case report - Mari Uomoto; Aya Tokinaga‐Uchiyama; Natsuko Kobayashi; Mika Okuda (Clinical Case Reports, 2023)
Key Clinical Message Transvaginal uterine restoration of nonpuerperal uterine inversion is difficult; there are risks of heavy bleeding and uterine perforation. In such cases, total hysterectomy and transfusion are inevitable. Abstract A 47‐year‐old woman with profuse genital bleeding, diagnosed with nonpuerperal uterine inversion caused by a uterine fibroma, underwent emergency surgery. Uterine perforation occurred during transvaginal uterine restoration, revealed by laparoscopy. Bleeding persisted and blood transfusion volume increased; therefore, a total hysterectomy was performed for hemostasis.